Sobre o amor em Graciliano Ramos - Guedes, Debora Carla Santos (2009)
In Caetés, São Bernardo e Angústia, Graciliano Ramos talks about the destructive power of love. Desire and passion are agents of jealousy, hate and death. João Valério, Paulo Honório and Luís da Silva, narrators and characters, each one in his own way, construct deformed images of his beloved. These narrators detain the art of writing and consequently power. Then, Luísa, Madalena e Marina are speechless women. Therefore, in these books, love has no place among affectionate lack, domination and violence